Hope for the future: Sowing the seeds for agricultural research in Somalia - Haji, H.; Longley, K. (2010)
The CGIAR Regional Collective Action for Eastern and Southern Africa (ESA) recently supported the Somali Agricultural Technical Group (SATG) in organizing workshops in Hargeisa and Nairobi to identify ways to promote agricultural research in Somalia. The workshops were held under Flagship Program 4 which aims to enhance food security in ESA countries affected by natural disaster and/or conflict through research-related activities that contribute towards effective and appropriate emergency preparedness, relief and recovery interventions.